Effects of a very short-term preseason training procedure on the fitness of soccer players - Meckel, Y.; Harel, U.; Michaely, Y.; Eliakim, A. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of the study was to examine the effect of a very short-term training program on the immediate and late changes in the fitness level of young soccer players during the pre-season period.